PENGARUH PEMBIAYAAN MUDHARABAH, MUSYARAKAH, DAN MURABAHAH TERHADAP PROFITABILITAS BPRS DI DAERAH TAPAL KUDA JAWA TIMUR - Ningsih, Wiwik Fitria; Yusuf, Muhammad Angga; Handayani, Yuniorita Indah (LP2M Institut Teknologi dan Bisnis Asia Malang, 2023)
This study aims to analyze the effect of mudharabah, musyarakah and murabahah financing on the profitability of BPRS in the Tapal Kuda area with the variables studied are Mudharabah financing, Musyarakah financing and Murabahah financing and using the NPM ratio. The research method used is descriptive research with a quantitative approach. The population used is 7 Islamic Rural Banks and the sample used is 3 Islamic Rural Banks with purposive sampling technique including BPRS Asri Madani Nusantara Jember, BPRS Daya Artha Mentari Pasuruan, and BPRS Ummu Pasuruan during the period 2015 – 2019. Sources of data obtained from the results of the related BPRS publications and through the official OJK website. The type of data obtained is secondary data based on the results of the BPRS annual financial report. The analytical tool used is multiple linear regression analysis. The results of this study indicate that partially mudharabah financing has no significant effect on profitability, musyarakah financing has no significant effect on profitability, while murabahah financing has no significant effect on profitability. Simultaneously, mudharabah, musyarakah, and murabahah financing have no significant effect on profitability.